Voices of Play : Miskitu Children's Speech and Song on the Atlantic Coast of Nicaragua - Minks, Amanda, 1974- (Book collections on Project MUSE., 2013)
While indigenous languages have become prominent in global political and educational discourses, limited attention has been given to indigenous children's everyday communication. This book is a study of multilingual play and performance among Miskitu children growing up on Corn Island, part of a multi-ethnic autonomous region on the Atlantic Coast of Nicaragua. Corn Island is historically home to Afro-Caribbean Creole people, but increasing numbers of Miskitu people began moving there from the mainland during the Contra War, and many Spanish-speaking mestizos from western Nicaragua have also settled there. Miskitu kids on Corn Island often gain some competence speaking Miskitu, Spanish, and Kriol English. As the children of migrants and the first generation of their families to grow up with television, they develop creative forms of expression that combine languages and genres, shaping intercultural senses of belonging. Voices of Play is the first ethnography to focus on the interaction between music and language in children's discourse. The author weaves together Latin American, North American, and European theories of culture and communication, creating a transdisciplinary dialogue that moves across intellectual geographies. The analysis in this work shows how music and language involve a wide range of communicative resources that create new forms of belonging and enable dialogue across differences. Miskitu children's voices reveal the intertwining of speech and song, the emergence of "self" and "other," and the centrality of aesthetics to social struggle.--description from publisher's website